Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Hi-C metagenomics facilitate comparative genome analysis of bacteria and yeast from spontaneous beer and cider - Ignat V. Sonets; Mikhail A. Solovyev; Valeriia A. Ivanova; Petr A. Vasiluev; Aleksey V. Kachalkin; Sofia D. Ochkalova; Anton I. Korobeynikov; Sergey V. Razin; Sergey V. Ulianov; Alexander V. Tyakht (Food Microbiology, 2024)

Estimating range disjunction time of the Palearctic Admirals (Limenitis L.) with COI and histone H1 genes - Vladimir I. Solovyev; Vladimir V. Dubatolov; Valeriya Y. Vavilova; Oleg E. Kosterin (Organisms Diversity & Evolution, 2022)

Localization of the proteinase inhibitor activity in the fish cestode Eubothrium rugosum - Galina I. Izvekova; Tatyana V. Frolova; Evgeny I. Izvekov; Elena N. Kashinskaya; Mikhail M. Solovyev (Journal of Fish Diseases, 2021)
The mechanisms enabling fish tapeworms to avoid proteolytic attacks by digestive enzymes of their fish host have been studied in less detail compared with mammalian cestodes. This study aimed to assess the inhibitory ability towards trypsin and chymotrypsin in Eubothrium rugosum, an intestinal parasite of burbot Lota lota , and establish its localization in the tapeworm. To this end, the worms were treated with Triton X‐100 followed by differential centrifugation to isolate the tegumental brush border membrane. The protease inhibitory abilities of the worms were mostly determined by their excretory/secretory products released into the incubation medium. These inhibitory abilities proved to be linked mainly with the brush border fractions. Notably, the per cent inhibition of both studied digestive enzymes (trypsin and chymotrypsin) hardly depended on the duration of the parasite exposure in the incubation medium, probably due to intermittent glycocalyx renewal. Improved knowledge on functions of the excretory/secretory proteins produced by fish tapeworms may contribute to a better understanding of host–parasite relations and development of new approaches to the treatment and prevention of diseases caused by pathogenic helminths.

Composition of the microbial communities in the gastrointestinal tract of perch ( Perca fluviatilis L. 1758) and cestodes parasitizing the perch digestive tract - Elena N. Kashinskaya; Evgeniy P. Simonov; Galina I. Izvekova; Aleksey N. Parshukov; Karl B. Andree; Mikhail M. Solovyev (Journal of Fish Diseases, 2020)
Using the approach of sequencing the V3‐V4 region of the 16S rRNA gene, we have analysed the bacterial diversity associated with the distinct compartments of the gastrointestinal tract of perch ( Perca fluviatilis ) and cestodes ( Proteocephalus sp.) parasitizing their digestive tract. The dominant microbiota associated with cestodes ( Proteocephalus sp.) was represented by bacteria from the genera Serratia , Pseudomonas and Mycoplasma . By comparing the associated microbiota of perch and cestodes, a clear difference in bacterial composition and diversity was revealed between the community from the stomach content and other parts of the gastrointestinal tract of fish. Microbiota associated with cestodes was not significantly different in comparison with microbiota of different subcompartments of perch (mucosa and content of intestine and pyloric caeca) (ADONIS, p > .05) excluding microbiota of stomach content (ADONIS, p ≤ .05). PICRUSt‐based functional assessments of the microbial communities of perch and cestodes indicated that they mainly linked in terms of metabolism and environmental information processing and could play an important role in the nutrition and health of host.

Selective Heterozygous Advantage of Carriers of с.-23+1G>A Mutation in GJB2 Gene Causing Autosomal Recessive Deafness 1A - A. V. Solovyev; N. A. Barashkov; F. M. Teryutin; V. G. Pshennikova; G. P. Romanov; A. M. Rafailov; N. N. Sazonov; L. U. Dzhemileva; M. I. Tomsky; O. L. Posukh; E. K. Khusnutdinova; S. A. Fedorova (Bulletin of Experimental Biology and Medicine, 2019)

Application of stable isotopic analyses for fish host–parasite systems: an evaluation tool for parasite-mediated material flow in aquatic ecosystems - Gen Kanaya; Mikhail M. Solovyev; Shuichi Shikano; Jun-ichi Okano; Natalia M. Ponomareva; Natalia I. Yurlova (Aquatic Ecology, 2019)

Ultrasound Treatment of Infected Wounds: Situation and Perspectives - D. A. Solovyev; S. I. Shchukin; S. P. Skvortsov; A. P. Nikolaev; P. V. Luzhnov (Biomedical Engineering, 2019)

Dependence of pH values in the digestive tract of freshwater fishes on some abiotic and biotic factors - M. M. Solovyev; G. I. Izvekova; E. N. Kashinskaya; E. Gisbert (Hydrobiologia, 2018)

Structure of freshwater zooplankton communities from tundra waterbodies in the Lena River Delta, Russian Arctic, with a discussion on new records of glacial relict copepods - E. Abramova; I. Vishnyakova; J. Boike; A. Abramova; G. Solovyev; F. Martynov (Polar Biology, 2017)

Opinions of hearing parents about the causes of hearing impairment of their children with biallelic GJB2 mutations - Aisen V. Solovyev; Lilya U. Dzhemileva; Olga L. Posukh; Nikolay A. Barashkov; Marita S. Bady-Khoo; Semen L. Lobov; Natalya Yu. Popova; Georgii P. Romanov; Nikolay N. Sazonov; Alexander A. Bondar; Igor V. Morozov; Mikhail I. Tomsky; et al. (Journal of Community Genetics, 2017)

Range of a Palearctic uraniid moth Eversmannia exornata (Lepidoptera: Uraniidae: Epipleminae) was split in the Holocene, as evaluated using histone H1 and COI genes with reference to the Beringian disjunction in the genus Oreta (Lepidoptera: Drepanidae) - Vladimir I. Solovyev; Vera S. Bogdanova; Vladimir V. Dubatolov; Oleg E. Kosterin (Organisms Diversity & Evolution, 2015)

Feeding habits and ontogenic changes in digestive enzyme patterns in five freshwater teleosts - M. M. Solovyev; E. N. Kashinskaya; G. I. Izvekova; E. Gisbert; V. V. Glupov (Journal of Fish Biology, 2014)
Feeding habits and the activity of digestive enzymes (total alkaline proteases, α ‐amylase and lipase) from dace Leuciscus leuciscus , roach Rutilus rutilus , Prussian carp Carassius auratus gibelio , perch Perca fluviatilis and pikeperch Sander lucioperca fry were studied in the Malye Chany Lake–Kargat Estuary (western Siberia, Russia). The diet of fry from all studied species was mainly composed of chironomid larvae and zooplanktonic organisms ( i.e. cladocera and copepoda), whereas carnivorous species such as P. fluviatilis and S. lucioperca also preyed on fry from other fishes while detritus and microalgae were also important in the diet of ommivorous species. When comparing diet similarity (Sørensen–Dice index, Q S ) among fry at different stages of development, both omnivorous and carnivorous species showed a high level of similarity (0·67 Q S Q S α ‐amylase:total proteases (A:P) values higher than 1 in omnivorous species and lower (A:P ≤ 1) in carnivorous species.

Erratum to: Variations in the activity of digestive enzymes along the intestine of the burbot Lota lota expressed by different methods - Galina I. Izvekova; Mikhail M. Solovyev; Elena N. Kashinskaya; Evgeny I. Izvekov (Fish Physiology and Biochemistry, 2013)

Variations in the activity of digestive enzymes along the intestine of the burbot Lota lota expressed by different methods - Galina I. Izvekova; Mikhail M. Solovyev; Elena N. Kashinskaya; Evgeny I. Izvekov (Fish Physiology and Biochemistry, 2013)

Genome sequences of poa semilatent and lychnis ringspot hordeiviruses - E. I. Savenkov; A. G. Solovyev; S. Y. Morozov (Archives of Virology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Analysis of mutation rates in the SMCY/SMCX genes shows that mammalian evolution is male driven - A. I. Agulnik; C. E. Bishop; J. L. Lerner; S. I. Agulnik; V. V. Solovyev (Mammalian Genome, 1997)